A convenient synthesis of 5′-triantennary N-acetyl-galactosamine clusters based on nitromethanetrispropionic acid. Issue 9 (1st May 2016) - Migawa, Michael T.; Prakash, Thazha P.; Vasquez, Guillermo; Wan, W. Brad; Yu, Jinghua; Kinberger, Garth A.; Østergaard, Michael E.; Swayze, Eric E.; Seth, Punit P.
Graphical abstract: Abstract: A convenient method for the synthesis of several triantennary GalNAc clusters based on a nitromethanetrispropionic acid core was developed. The synthetic approach involves pentafluorophenolic ester intermediates which can be used in a one-pot, seven reaction procedure to quickly prepare a variety of triantennary GalNAc conjugated ASOs. The GalNAc clusters were conjugated to the 5′-end of an antisense oligonucleotide and evaluated for activity in primary mouse hepatocytes where they showed ∼10-fold improvement in activity.